SPATIAL MODELINGG OF SOILL TEXTURE CLASSES FOR AL–NAJMI DISTRICT IN AL–MUTHANNA GOVERNORATE USING THE SPATIAL INTERPOLATION METHOD - A. A. Yassin; A. R. Jubier; A. K. Fazza (مجلة الأنبار للعلوم الزراعية, 2025)
This study was conducted to determine the spatial distribution of soil texture classes and their particales of sand, silt, and clay. The lands of the study area are confined between longitudes 440 26' 00" to 450 10' 00" east and two latitudes 310 30' 00" to 310 40' 00" north, After the field visit, the auger drilling sites were determined to a depth of 0 - 30, 30 - 60, 60 – 90, 90 -120 m, which the detection was done, about 8 pedons, and the coordinates of the sites and pedons were determined with a GPS device. Then samples were obtained from each approved site and brought to the laboratory and prepared ,then the texture types were determined on the standard texture triangle, as the results showed a variation in the distribution of Types of textures: The percentage of sand ranged between 0.88 -76.78%, and the percentage of silt ranged between 11.16 - 79.58%, It is noted that the percentage of partical silt It is high in the soil of the study area .while the percentage of clay in these soils ranged between 4.0 - 61.0%. The results showed that the dominant type of texture in the soil of the study area is the Silt type. Clay Loam with a percentage of 34.87%, followed by Silt Clay with a percentage of 25.56%, The other types of textures are ranked in terms of dominance. The lowest percentage in terms of dominance was the Sand Loam type with a percentage of 5.92% and the Clay type with a percentage of 0.21%.